2022
DOI: 10.3389/fpsyg.2022.751041
|View full text |Cite
|
Sign up to set email alerts
|

Genetics in the ADHD Clinic: How Can Genetic Testing Support the Current Clinical Practice?

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is a neurodevelopmental disorder with a childhood prevalence of 5%. In about two-thirds of the cases, ADHD symptoms persist into adulthood and often cause significant functional impairment. Based on the results of family and twin studies, the estimated heritability of ADHD approximates 80%, suggests a significant genetic component in the etiological background of the disorder; however, the potential genetic effects on disease risk, symptom severity, and persisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 223 publications
0
5
0
Order By: Relevance
“…Although there were no obvious psychiatric comorbidities in our sample, adult ADHD is often associated with psychiatric comorbidities and a high prevalence of depression has also been reported ( 39 ). Common genetic factors for ADHD and depression have been reported as contributing to this phenomenon ( 40 ). Therefore, we speculate that abnormalities of these regions seem to be associated with not only cognitive disability but also susceptibility to depressive disorder in adult ADHD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there were no obvious psychiatric comorbidities in our sample, adult ADHD is often associated with psychiatric comorbidities and a high prevalence of depression has also been reported ( 39 ). Common genetic factors for ADHD and depression have been reported as contributing to this phenomenon ( 40 ). Therefore, we speculate that abnormalities of these regions seem to be associated with not only cognitive disability but also susceptibility to depressive disorder in adult ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…The corticostriatal projections are critical components of forebrain circuits that are extensively involved in motivated behavior ( 28 ). Not only decreased connectivity but also overconnectivity may also disrupt structural connectivity and information transfer, and some studies demonstrated overconnectivity in patients with ASD ( 40 ). The corticostriatal circuits have been linked to dopaminergic pathways that connect the striatum to the prefrontal cortex and other areas, and dysfunction of these circuits has been linked to impairments in cognitive functions and the ability to adapt behavior to changing circumstances ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genes encoding the dopamine receptors (e.g., DRD2 and DRD4), dopamine transporter (DAT1), and monoamine oxidase (MAOA) enzymes, such as catechol-Omethyltransferase (COMT) and dopamine beta-hydroxylase (DBH), are the most studied [12][13][14]. However, the influence of genetics on disease risk needs to be better understood [15]. Children with ADHD can also exhibit hostility or anger and aggressive behavior.…”
Section: Factors Associated With Adhdmentioning
confidence: 99%
“…14 Neuroimaging, genetic, and electrophysiological studies have been conducted aiming to discover pathophysiological and biological markers for ADHD. 15,16 Quantitative electroencephalography (QEEG) can detect subtle changes in EEG that are difficult to discriminate visually, and it is known to have greater accessibility and safety compared with other examination methods. 17,18 Accordingly, there have been attempts to use QEEG to distinguish between normal children and children with ADHD.…”
Section: Introductionmentioning
confidence: 99%